Mental model development of preservice science teachers with slow-motion animation and visual material: The case of circulatory system - Emine Büşra Bilginer; Emine Uzun (Journal of Pedagogical Research, 2022)
This case study aimed to examine whether slow-motion animation and visual materials provide to enhance mental model developments of preservice science teachers (PSTs). A total of 34 PSTs (16 in visual material group and 18 in slow-motion animation group) participated into the study. A mental model application related to circulatory system subject, an observation form, and an open-ended interview form based on the slow-motion animation process were used to collect data. Content analysis was performed to systematically analyze the data. The results showed that the correct model-correct explanation ratios of the PSTs in the slow-motion animation group were higher than those in the visual material group. Based on the observations, the PSTs performed the slow-motion animation in five steps, and the group generally demonstrated these behaviors at the desired level. PSTs expressed their opinions about the slow-motion animation technique in interviews as learning by doing, having fun while learning, and technology supporting and facilitating learning. Using slow-motion animation in education is recommended since it creates an active learning environment for students.